TRUST TRANSFER IN ONLINE TRANSPORTATION - Made Purnami, Ni (STIE PGRI Dewantara Jombang, 2023)
Building trust in online transportation services is crucial due to the inherent unfamiliarity between customers and drivers. This study specifically aims to explore the dynamics of trust transfer within the realm of online transportation and its subsequent impact on fostering customer loyalty. The population in this study consists of online transportation users in Bali. The number of samples examined is 300 individuals using purposive sampling method. Data collection was executed through an online platform utilizing a Google form. Subsequently, the collected data underwent analysis using Smart PLS. The study's outcomes are noteworthy, indicating that: (1) Trust in the application has a positive effect on building trust in drivers; (2) Trust in the application significantly influences and promotes customer loyalty; (3) Trust in drivers plays a pivotal role in increasing customer loyalty; and (4) Trust in drivers acts as a partial mediator in the relationship between trust in the application and trust in drivers. These findings contribute valuable insights into the intricacies of trust dynamics within the online transportation sector.